Analisis Efisiensi Pemasaran Karang Hias di Pulau Panggang, Kabupaten Administrasi Kepulauan Seribu Marketing is one of the main interesting problem of karang hias (artifICial coral) business in Pulau Panggang. Some of artificial coral are gathered and then sole by fishennan to the collector who come to Pulau Panggang periodically. Among of species of artificial coral marketed from Pulau Panggang were called karang hias Jamur Mangkok, karang hias Babut Hijau, karang hias Pipa Salim and karang hi - Henrikus Passlamanto; Popong Nurhayati; Iis Diatin (Buletin Ekonomi Perikanan, 2006)
Analisis Efisiensi Pemasaran Karang Hias di Pulau Panggang, Kabupaten Administrasi Kepulauan Seribu Marketing is one of the main interesting problem of karang hias (artifICial coral) business in Pulau Panggang. Some of artificial coral are gathered and then sole by fishennan to the collector who come to Pulau Panggang periodically. Among of species of artificial coral marketed from Pulau Panggang were called karang hias Jamur Mangkok, karang hias Babut Hijau, karang hias Pipa Salim and karang hias Nanas Mata. There are many marketing institutional involved in artificial coral marketing from Pulau Panggang. They have a big role to deliver karang hias from fISherman to the consumer. The aims of this research are : 1) to identify the pattern of karang hias marketing channel that occurred in Pulau Panggang, 2) to analyze marketing efficiency of karang hias in Pulau Panggang: include of market structure, market behavior and marketing margin. Result of this research showed that there are five patterns of marketing chamef in Pulau Panggang. Marketing instjutional that i!1volved in distribution of karang hias to the consumer consisted of fishermen, coIlector, merchant, exporter, and retailer. Market structured of karang hias tend to form imperfectly competition. Market behavior showed that in functional martfel activities fisherman have got a low price and low of fishermen's share. Market institutional of karang hias didn't get the spread of profit, cost of marketing was relatively high and marketing margin was also high enough. Those market structure,market behavior and marketing margin Rlcated that marketing of karang hias in Pulau Panggang, Kabupaten Administrasi Keputauan Semu was inefficient.